Leaves of neotropical savanna tree species are more heat-tolerant than leaves of semi-deciduous forest species - Silva, Bianca Helena Porfírio da [UNESP]; Rossatto, Davi Rodrigo [UNESP] (Springer Nature, 2022)
Increases of air temperature due to global warming suggest that plants could be exposed to temperatures above their optimum range for performing specific physiological functions in the future. Declines in carbon exchange rates would lead to significant decreases in species performance, particularly in those lacking traits associated to heat tolerance. Savannas and semi-deciduous forests are ecosystems with high biological diversity, scattered throughout the Neotropical landscape, and very dynamic areas controlled by species traits. Significant increases in air temperatures can affect such areas if plant species of these forests lack heat tolerance. We performed heat tolerance assays to obtain T50 values of the photosystem II (PSII) of 30 Neotropical tree species from a savanna (15 species) and a semi-deciduous forest (15 species). Our goal was to test whether the typical savanna species are more heat-tolerant than semi-deciduous forest species. We also assessed if T50 was correlated with leaf morphological traits such as specific leaf area and leaf thickness. We found savanna tree leaves with lower specific leaf area, higher thickness, and higher T50 values than semi-deciduous forest plants (49.36 °C vs. 47.65 °C, respectively). Specific leaf area was negatively correlated to T50 values. Our findings suggest that semi-deciduous forest species would be more affected by temperature increases than savanna species. Whereas species traits play an important role in the dynamics of forest–savanna areas, savanna species would be favored under warmer temperatures.
Keywords: Atlantic Forest; Cerrado; Heat tolerance; Specific leaf area